PENGARUH PROFITABILITAS, LIKUIDITAS DAN GOOD CORPORATE GOVERNANCE (GCG) TERHADAP NILAI PERUSAHAAN SEKTOR PERBANKAN DI INDONESIA - Echa HIKMAWATI SUNDARI; Felisitas Defung; Musdalifah Azis (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2020)
Echa Hikmawati Sundari. Effect of Profitability, Liquidity and Good Corporate Governance (GCG) on the Value of Corporate Banking in Indonesia Registered on the IDX. Supervised by: F, Defung and Dr. Musdalifah Aziz, SE., M.Sc.    The purpose of this study is to analyze profitability, liquidity and good corporate governance, using data from banking companies listed on the Indonesia Stock Exchange during the study year. The population consists of 43 companies in the Banking Sector in the 2014-2017 period. The sample consisted of 24 companies that had been sampled based on purposive sampling technique. The variable of this research is to represent profitability measured by Return on Assets (ROA), Liquidity measured by Loan to Deposit Ratio (LDR) and good corporate governance is proxied through GCG self assessment values published by the company in the annual report. The method of this research is multiple linear regression analysis using SPSS Software version 21. The results of the study show that profitability has a positive and significant effect on firm value. Liquidity has a negative and significant effect on firm value. While Good corporate governance has no significant effect on firm value.